Liquid hydrogen tests of a sub-scale launcher upper stage feed line evaporation cooler. (May 2019) - Isselhorst, Armin; Suslov, Dmitry; Riccius, Jörg
Abstract: Propellant conditioning is a challenge for the development of cryogenic upper stages with re-ignitable main-engines. The VINCI engine needs for its operation propellant under specific conditions w.r.t. pressure and temperature to avoid cavitation inside the propellant pumps. After long ballistic phases the temperature of the propellant can increase to the respective saturation temperature of the tank pressure due to radiative solar heating. By means of the proposed feed line evaporation cooler 1 stly the usual release of the tank pressure for thermally conditioning the propellant and 2 ndly the follow-on re-pressurization of the tank with Helium can be avoided. Furthermore, this feedline evaporation cooler allows cooling only the propellant amount that is actually consumed by the engine. In this paper the design of the EC test unit, the LH2 test bench and respective results of the tests performed with LH2 will be presented in order to demonstrate the technology's capability and readiness. Additionally, a possible design and assembly on the A6 upper stage propulsion module is suggested. Highlights: Chosen Al cooler design is capable to fulfill the Ariane 6 strength requirements. Nozzles, capillary tubes, related dimensions of sub-scale cooler already real scale. Applied 2-phase model is well applicable for involved Hydrogen flow boiling process. Evaporation cooler fulfills 5 K cool down requirement with estimated efficiency. mass saving for A6 GTO single-re-ignition is 87 kg, for LEO dual re-ignition 224 kg.